The role of sulfur emission from the petroleum industry on ultrafine particle number concentration in Singapore - Hou, Suyi (2023)
Ultrafine particles, defined as particles with a diameter (dp) smaller than 100 nm, serve as an important component of cloud condensation nuclei, in addition to impacting human health. The dominant sources of ultrafine particles include traffic emissions and nucleation. Singapore is a tropical city that hosts petrochemical industries. To identify the sources of ultrafine particles, a year-long observation of the number size distribution was conducted in Singapore in 2018 and 2019. The concentrations of CO, CO2, CH4, and SO2 were also monitored. The particle number concentration during the southwest monsoon season was high, while that during the northeast monsoon period was relatively low. The CO concentration increased during the morning traffic rush hours, which was associated with relatively minor enhancements in ultrafine particle number concentration. The events for a high number concentration of the Aitken mode particles (dp < 50 nm) were identified during high SO2 concentration periods. The SO2 concentration was high during the afternoon because the sea breeze transported the emissions from the coastal industrial area to the observation site. The enhancements in CH4 from its background level (ΔCH4) and SO2 had a quasi-inverse relationship, as the major emission sources of these two chemical species were different. The particle number concentration (dp > 50 nm) correlated with the enhancements in CO concentration (ΔCO) for CH4-dominant air masses, suggesting that incomplete combustion processes, such as traffic emission, are important for the size range. Conversely, the number concentration of the Aitken mode particles (dp < 50 nm) increased for SO2-dominant air masses, suggesting the importance of industrial plume.